ANT COLONY OPTIMIZATION WITH DOUBLE SELECTIONS FOR SOLVING INTEGRATED SCHEDULING PROBLEM IN MANUFACTURER - Abusini, Sobri; Sukmarini, Mita Akbar; Karim, Corina (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2019)
In this paper, we studied ant colony optimization for solving integrated scheduling of production and distribution problems. We improved the ant colony optimization by adding double selections, there are, roulette wheel and elitism selections. Roulette wheel selection is used to determine the path where ants pass through before knowing pheromone information in that path. Meanwhile, elitism selection is used to keep the best solution before the more optimum solution obtained. Then, ant colony optimization and improved ant colony optimization are implemented in solving integrated scheduling of production and distribution problem in PT. BFPI. The aim of this paper is to achieve optimum production and distribution schedule in order to minimize the total cost of production and distribution. We also compare performance of both applied methods and draw the conclusion. The results show that the method we proposed has more advantage.